Jasmonic Acid-Dependent Defenses Play a Key Role in Defending Tomato Against Bemisia tabaci Nymphs, but Not Adults - Zhang, Peng-Jun; He, Yu-Chen; Zhao, Chan; Ye, Zi-Hong; Yu, Xiao-Ping (Frontiers in Plant Science, 2018)
The silverleaf whitefly Bemisia tabaci is an important and invasive crop pest in many countries. Previous laboratory studies with Arabidopsis thaliana demonstrated that B. tabaci can suppress jasmonic acid (JA) defenses and thereby enhance B. tabaci performance. Whether B. tabaci has similar effects on other plants and in the field is unknown. In the present study, we found that, relative to wild-type (WT) tomato plants, transgenic tomato mutants that activated JA defenses (35s::prosys) or impaired JA defenses (spr-2 and def-1) did not affect the survival or reproduction of B. tabaci adults in growth chamber experiments. In contrast, tomato mutants that activated JA defenses slowed B. tabaci nymphal development, while mutants that impaired JA defenses accelerated nymphal development. These effects of JA defenses on nymphal development were also documented under semi-field conditions. Changes in the expression of defense genes and in the production of phytohormones indicated that B. tabaci can suppress JA-dependent defenses after infestation for > 72 h. The suppression of JA was correlated with the induction of SA in B. tabaci-infested leaves under laboratory and under semi-field conditions. If SA signaling was blocked, JA accumulation increased in infested leaves and B. tabaci nymphal development was delayed. These results indicate that, although JA signalling helps in mediating tomato responses against B. tabaci nymphs, B. tabaci can inhibit JA biosynthesis and its action in an SA-dependent manner.